Leadership and Commitment to Service Quality in Pakistani Hospitals: The Contingent Role of Role Clarity. (October 2020) - Pahi, Munwar Hussain; Ahmed, Umair; Sheikh, Abdullah Zafar; Dakhan, Sarfraz Ahmed; Khuwaja, Faiz Muhammad; Ramayah, T.
The health care system is usually a reflection of the human development and prosperity index of a country. In particular, a sound health care system is generally deemed essential for providing quality service delivery to service users. Pakistan, in this respect, is lagging even after implementing the district health management model of World Health Organization (WHO). In particular, the province of Sindh reports a higher level of dissatisfaction among the service recipients and, therefore, remains a core concern for the concerned authorities. This study, therefore, aims to investigate the levels of employees' commitment to service quality in Pakistan's health care sector. A quantitative survey method was adopted to collect data from 315 medical officers working in 43 public-sector hospitals in Sindh, Pakistan. The data were analyzed using the partial least squares structural equation modeling (PLS-SEM) technique and Smart PLS 3 software. Based on cognitive dissonance theory and path-goal theory, the present study investigated the role of leadership styles in influencing commitment to service quality with the moderation of role clarity. The findings lend support to the direct hypothesized relationships of transformational and transactional leadership with commitment to service quality. The study found significant support for all the hypothetical relationships except laissez-faire leadership's direct link with commitment to service quality. While role clarity was found to moderate the relationships of two leadership styles, namely, transformational leadership and laissez-faire leadership with commitment to service quality, there was no such moderating effect for the relationship between transactional leadership and commitment to service quality. These findings offer useful theoretical and managerial implications on the importance of leadership styles in influencing commitment to service quality and provide the basis for future research.